PENDAMPINGAN PENGUATAN MINAT BELAJAR MELALUI METODE REWARD TEKNIK TOKEN ECONOMY PADA SISWA SEKOLAH DASAR KELURAHAN HABARING HURUNG - Aldi Winanto; Noor Hujjatusnaini (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This mentoring program aims to provide support for strengthening children's interest in learning through the token economy technique reward method for elementary school students in Habaring Hurung Village. This mentoring program is part of the Thematic Real Work Lecture program service activity which is carried out for 3 days with a pretest and posttest program design. Data collection is done by means of observation, task training, and the application of the reward method using the token economy technique. The final result of the program implementation shows that there is an increase in student interest in learning after the token economy technique reward method is applied. The pleasure indicator increased by 30 points, the engagement indicator increased by 27 points, the interest indicator increased by 26 points, and the attention indicator increased by 26 points. Thus, it can be concluded that the learning interest of grade 1 students at SDN 1 Habaring Hurung can be increased through the application of the token economy technique reward method